A purely functional Imaging based approach for transcortical resection of lesion involving the dominant atrium: Towards safer, imaging-guided, tailored cortico-leucotomies. (April 2018) - Frati, Alessandro; Pesce, Alessandro; D'Andrea, Giancarlo; Fraschetti, Flavia; Salvati, Maurizio; Cimatti, Marco; Esposito, Vincenzo; Raco, Antonino
Highlights: The left atrium surgery appears at high risk of new postoperative deficits. DTI provides reliable eloquent white matter fiber bundles reconstructions. On the ground of DTI reconstructions a safe surgical planning is possible. Brain edema can negatively affect the reliability of DTI reconstructions. A purely Functional transcortical approach to the left atrium appears promising. Abstract: Background and study object: The Dominant Atrium (DA) is a crossroad of eloquent white matter bundles difficult to preserve with a standard "anatomical" approach. The aim of this work is to evaluate the results of a cohort of patients who underwent surgery with the aid of a purely functional MRI and DTI-based approach. Materials and methods: 43 patients suffering from lesions involving the DA have been included in the final cohort and studied in regards to quality of life (KPS); a special attention was lent on the incidence of new or worsening of preexisting neurological deficits, with a focus on motor, visual and speech disturbances after the surgical treatment. Patient, surgery and lesion-related data were recorded to identify the relationships with outcome. Eloquent areas fMRI and the course of Arcuate Fasciculus (AF), Inferior frontooccipital fasciculus (IFOF), Optic radiation (OR) and corticospinal tract (CST) have been investigated with preoperative MRI sequences and DTI reconstruction. Results: The final cohort consisted of 43 patients, 19 males and 24 females; average age was 56.8 years. We recorded 9 transient and 3 permanent postoperative deficits, only one of those was caused by an edema interference with DTI reconstruction. Preoperative functional status, histology and volume of the lesion proved to be independent factors affecting results. Conclusions: A purely functional surgical approach to the DA provided promising preliminary results. A direct DTI-fMRI visualization of the eloquent structures proximal to DA allows surgeon to conceive an ultra-precise and "tailored" cortico-leucotomy for an optimal exposure of the lesion.